(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the historical stage of development and the formation of youth policy in pre and post Independence period of Uzbekistan. The first and true state youth policy is compared. Institutions of civil society, their historical experience and role in supporting youth in the country over the years of Independence are also considered.